Università oggi: problemi aperti - Striano, Maura (Studi sulla Formazione/Open Journal of Education, 2019)
Within current scenarios the university seems to have progressively lost its original mission and vocation, according to the logic of a “learning economy” in a neolibera perspective, which reduces it to an agency of certification and training. It is necessary to overcome this trend, by reflecting on the role and functions of the university according to a democratic frame of reference,, which focuses on the acknowdgment of the individual right to education intended as a process aimed at sustaining personal and social growth as well as on the necessity to cultivate awareness and partecipative engagement in the public life.